Geometric Modeling of a Mobile Vegetable-Growing Settlement’s Land Plots - Juraev, Tojiddin; Saidov, Mirzoqul; Pancha, Yuli (INTI Journal, 2026)
The article involves the development of a mobile vegetable-growing settlement’s conception, designed to comprehensively address a range of economic, social and environmental issues. The article relates to sustainable agricultural development. It is to address the issues of creating an adaptable environment in agricultural fields for the effective use of precision agriculture in crop production. The aim of the paper is to develop the concept of a mobile vegetable-growing settlement, designed to make more efficient use of the precision farming systems in a new context by creating an adaptable agricultural field’s environment. The concept was developed using geometric modeling based on a systems analysis of the situation. The result is a mobile and scalable land lot allocation system. Such a field distribution system creates an adaptable environment for more efficient use of precision agriculture systems, in both formats: traditional and modern crop production